1999
DOI: 10.1149/1.1391599
|View full text |Cite
|
Sign up to set email alerts
|

Fourier Transform Infrared Characterization of Downstream Gas‐Phase Species Generated by Tetraethylorthosilicate/Ozone Atmospheric Pressure Reactions

Abstract: The effluent gas-phase composition from the atmospheric pressure reaction between tetraethylorthosilicate (TEOS) and ozone was investigated as a function of reactor temperature and initial reactant molar ratio. Online, continuous quantitative determination of gas species was achieved using Fourier transform infrared techniques. TEOS decomposition was a function of initial ozone concentration and reactor temperature. Ozone enhanced TEOS decomposition was found to generate carbon monoxide, carbon dioxide, formic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…The chemical vapor deposition (CVD) of SiO 2 has been widely studied since thirty years (Kotani et al, 1989), mainly in semiconductor manufacturing as gate dielectrics (Inoue et al, 1987;Ding et al, 2001), and more recently in membrane-based gas separation and energy harvesting (Choi et al, 2013;Liang et al, 2019;Azizi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical vapor deposition (CVD) of SiO 2 has been widely studied since thirty years (Kotani et al, 1989), mainly in semiconductor manufacturing as gate dielectrics (Inoue et al, 1987;Ding et al, 2001), and more recently in membrane-based gas separation and energy harvesting (Choi et al, 2013;Liang et al, 2019;Azizi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Zhang et al 26 used GC-MS for the characterization of the gas phase during the deposition of SiC from methyltrichlorosilane in the presence of H2, identifying HCl and SiCl4 molecules as by-products. In the same context, Arno et al 27 used online FT-IR analysis, detecting primarily carboxylic acids and water, among other compounds, during the SiO2 deposition from TEOS and O3. As for Si3N4 films, the gas phase characterization and deposition mechanisms from SiH4 and NH3 by photo-assisted CVD, or from SiH2Cl2 and NH3 by low-pressure CVD have been investigated by transient mass spectroscopy.…”
mentioning
confidence: 99%
“…Assignment of TEOS/O 3 Reaction Products. Previous researchers investigating the TEOS/O 3 process with FT-IR were able to observe gas-phase byproducts without interference from TEOS and identified acetic acid, formic acid, H 2 O, CO, and CO 2 . In those studies, there were no aldehydes (i.e., acetaldehyde and formaldehyde) detected; however, the authors suspected that the reason the aldehyde products were not observed was that they were being oxidized into the observed acetic acid and formic acid products .…”
Section: Resultsmentioning
confidence: 97%
“…FT-IR studies of the downstream effluent produced during the reaction of TEOS and O 3 have shown the species listed in Table to be present; however, acetaldehyde, the presumed ultimate source of these species, was not detected in these applications . In contrast to those studies, Mucha et al observed infrared spectroscopic evidence for acetaldehyde and acetic acid generation at temperatures of 247 °C in the downstream effluent.…”
Section: Introductionmentioning
confidence: 94%